Activation of Mg2+-dependent DNAzymes based on AP site-containing triplex for specific melamine recognition. Issue 22 (9th October 2015) - Wang, Ya; Zhang, Junying; Zhu, Linling; Lu, Linlin; Feng, Chongchong; Wang, Fengyang; Xu, Zhiai; Zhang, Wen
Abstract : A novel strategy for melamine recognition based on melamine binding-triggered triplex formation and DNAzyme activity regulation was developed. Abstract : Based on melamine binding-triggered triplex formation and subsequent activation of Mg 2+ -dependent DNAzymes, a novel strategy for DNAzyme regulation was proposed and developed for melamine recognition.